A Self-Powered and Chemically Responsive Triboelectric Nanogenerator Based on Surface Protonation in SrO 2 Nanopowder/Graphene Oxide/epoxy Composite for pH Sensing - Prasert Saengpoe; Wisut Supasai; Narong Amorntep; Chatree Nilnumpetch; Manussawee Nokkaew; Wattana Samanjit; Alongkot Treetong; Chanachot Saetang; Thitirat Charoonsuk; Phakkhananan Pakawanit; Te‐Wei Chiu; Saichon Sriphan; et al. (ACS Applied Nano Materials, 2025)
Practical implementation of triboelectric nanogenerators (TENGs) in autonomous systems is frequently impeded by their inadequate durability in chemically harsh environments. To address this limitation, we present a durable TENG utilizing a strontium dioxide nanopowders/graphene oxide/epoxy resin (SrO2 NPOs/GO/ER) composite, positioning SrO2 NPOs as an innovative, high-permittivity filler for triboelectric applications. By synergistically integrating the elevated dielectric constant of SrO2 NPOs with the interfacial polarization of GO NPOs, our optimized composite achieves an outstanding output of approximately 136 V and 2.3 μA/cm2 under a 100 N force, exceeding the performance of numerous advanced TENGs. Significantly, we convert a common degradation mechanism, i.e., surface protonation, into a functional sensing approach. The device leverages reversible protonation–deprotonation dynamics to convert environmental pH into distinct electrical signals, enabling self-powered, real-time pH sensing. The sensor exhibits excellent linearity (R2 > 0.97) across three distinct operational regions (pH 1–12), demonstrating high sensitivity to acidity changes. The device has demonstrated remarkable durability, completing approximately 11,000 mechanical cycles. Also, the proposed device serves high chemical durability, maintaining stable performance (up to 6000 cycles) after 24 h immersion in neutral and alkaline solutions. Our work establishes a resilient, multifunctional platform that simultaneously harvests energy and senses its chemical surroundings by reframing protonation as a design principle. This breakthrough paves the way for next-generation TENGs for use in environmental monitoring, resilient IoT networks, and adaptive self-powered electronics that can function under conditions where the chemical environment changes.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Dielectric materials and actuators